Green chemistry-assisted synthesis of biocompatible Ag, Cu, and Fe2O3 nanoparticles. (March 2020) - Jasrotia, T.; Chaudhary, S.; Kaushik, A.; Kumar, R.; Chaudhary, G.R.
Abstract: Green chemistry-assisted biocompatible copper (Cu), silver (Ag), and iron oxide (Fe2 O3 ) nanoparticles (NPs) synthesis along with surface modification using Koelreuteria apiculata is demonstrated in this research, for the first time. Appropriate analytical techniques were utilized to confirm the preparation, spherical morphology, and crystalline structure of each of the NPs. The antioxidant nature of synthesized NPs was evaluated using 2, 2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging. Besides, the antimicrobial activity was also performed using bacterial strains of Staphylococcus aureus, Escherichia coli, and Salmonella typhi. Aspergillus sp. was designed as marker specie for the antifungal studies. The outcomes of NPs exposure, analyzed with reference to Chlorella sp. of the algal family exhibit the numerical values around 833% for AgNPs, 497% of CuNPs, and 456% for Fe2 O3 NPs. Phytotoxicity assay performed on the seeds of Vigna radiata and Cicer arietinum further validate the accordant nature of NPs towards vivacity. Allium cepa was also used as a test model to ascertain the genotoxic effects of the NPs wherein the mitotic index (MI) was calculated for AgNPs, CuNPs, and Fe2 O3 NPs as 42.1, 51.7, and 54.2% respectively. The outcomes of this research proved the suitability and affordability of our NPs developed using green synthesis for new industrial applications of in-situ reduction of carcinogenic compounds from water and soil. Graphical abstract: Image 1 Highlights: Synthesis of silver, copper and iron(III) oxide nanoparticles with K. apiculata. Antioxidant profiling of nanoparticles was performed. Biocompatibility studies confirmed biocompatible nature of nanoparticles.